Caenorhabditis elegans homologue of Prox1/Prospero is expressed in the glia and is required for sensory behavior and cold tolerance. (12th July 2016) - Kage‐Nakadai, Eriko; Ohta, Akane; Ujisawa, Tomoyo; Sun, Simo; Nishikawa, Yoshikazu; Kuhara, Atsushi; Mitani, Shohei
Abstract : The Caenorhabditis elegans ( C. elegans ) amphid sensory organ contains only 4 glia‐like cells and 24 sensory neurons, providing a simple model for analyzing glia or neuron‐glia interactions. To better characterize glial development and function, we carried out RNA interference screening for transcription factors that regulate the expression of an amphid sheath glial cell marker and identified pros‐1, which encodes a homeodomain transcription factor homologous to Drosophila prospero /mammalian Prox1, as a positive regulator. The functional PROS‐1::EGFP fusion protein was localized in the nuclei of the glia and the excretory cell but not in the amphid sensory neurons. pros‐1 deletion mutants exhibited larval lethality, and rescue experiments showed that pros‐1 and human Prox1 transgenes were able to rescue the larval lethal phenotype, suggesting that pros‐1 is a functional homologue of mammalian Prox1, at least partially. We further found that the structure and functions of sensory neurons, such as the morphology of sensory endings, sensory behavior and sensory‐mediated cold tolerance, appeared to be affected by the pros‐1 RNAi. Together, our results show that the C. elegans PROS‐1 is a transcriptional regulator in the glia but is involved not only in sensory behavior but also in sensory‐mediated physiological tolerance. Abstract : We performed RNA interference (RNAi) screening for transcription factors that regulate the expression of an amphid sheath glial cell marker and identified pros‐1, which encodes a homeodomain transcription factor homologous to Drosophila prospero/mammalian Prox1, as a positive regulator. The functional PROS‐1::EGFP fusion protein was localized in the nuclei of the glia and the excretory cell but not in the amphid sensory neurons. We further found that the structure and functions of sensory neurons, such as the morphology of sensory endings, sensory behavior and sensory‐mediated cold tolerance, appeared to be affected by pros‐1 RNAi.